Nano-biotechnology: a new approach to treat and prevent malaria - Rahman K (Dove Medical Press, 2019)
Khaista Rahman,1,* Shahid Ullah Khan,2,* Shah Fahad,2,3 Ming Xian Chang,4,5 Aqleem Abbas,6 Wasim Ullah Khan,7 Lutfur Rahman,8 Zaheer Ul Haq,9 Ghulam Nabi,4,5 Dilfaraz Khan10 1College of Animal Sciences/State Key Laboratory of Agricultural Microbiology, Huazhong Agricultural University, Wuhan 430070, China; 2College of Plant Sciences and Technology/National Key Laboratory of Crop Genetic Improvement, Huazhong Agricultural University, Wuhan 430070, China; 3Department of Agriculture, The University of Swabi, Khyber Pakhtunkhwa, Anbar, Pakistan; 4State Key Laboratory of Freshwater Ecology and Biotechnology, Institute of Hydrobiology, the Chinese Academy of Sciences, Wuhan 430072, Hubei, China; 5University of the Chinese Academy of Sciences, Shijingshan District, Beijing, China; 6Provincial Key Lab of Plant Pathology of Hubei Province, Huazhong Agricultural University, Hongshan District, Wuhan 430070, China; 7School of Chemistry and Chemical Engineering, Sun Yat-Sen University, Guangzhou, China; 8Molecular Systematics & Applied Ethno Botany Lab (MoSEL), Department of Biotechnology, Quaid I Azam University, Islamabad, Pakistan; 9School of Chemistry and Chemical Engineering, Shanghai Jiao tong University, Shanghai, China; 10Institute of Chemical Sciences, Gomal University, Dera Ismail Khan, Pakistan *These authors contributed equally to this work Abstract: Malaria, the exterminator of ~1.5 to 2.7 million human lives yearly, is a notorious disease known throughout the world. The eradication of this disease is difficult and a challenge to scientists. Vector elimination and effective chemotherapy for the patients are key tactics to be used in the fight against malaria. However, drug resistance and environmental and social concerns are the main hurdles in this fight against malaria. Overcoming these limitations is the major challenge for the 21st-century malarial researchers. Adapting the principles of nano-biotechnology to both vector control and patient therapy is the only solution to the problem. Several compounds such as lipids, proteins, nucleic acid and metallic nanoparticles (NPs) have been successfully used for the control of this lethal malaria disease. Other useful natural reagents such as microbes and their products, carbohydrates, vitamins, plant extracts and biodegradable polymers, are also used to control this disease. Among these particles, the plant-based particles such as leaf, root, stem, latex, and seed give the best antagonistic response against malaria. In the present review, we describe certain efforts related to the control, prevention and treatment of malaria. We hope that this review will open new doors for malarial research. Keywords: malaria, vectors, chemotherapy, drug resistance, nano-biotechnology